Exploration of older and younger British adults' performance on The Awareness of Social Inference Test (TASIT). Issue 5 (13th April 2016) - Burdon, Paul; Dipper, Lucy; Cocks, Naomi
Abstract: Background: Social perception is an important skill. One assessment that is commonly used to assess social perception abilities is The Awareness of Social Inference Test (TASIT). The only normative data available for this test are for Australian younger adults. Despite no normative data being available for British adults, the test is widely used in the UK with older and younger adults. There is a growing body of research that suggests that older adults have difficulty with skills associated with social perception. There is therefore a need to determine whether British adults, and more specifically British older adults, perform similarly to the Australian normative TASIT scores available in the manual. Aims: To explore the differences between older and younger British adults' performance on TASIT, and to determine whether younger and older British adults perform similarly to the data from Australian adults in TASIT manual. Methods & Procedures: TASIT was administered to a total of 42 native British English speaking participants. The participants were split into two age groups 18–45 and 60–90 years. Comparisons were made between the two groups and the Australian data in TASIT manual. Outcomes & Results: The younger British and Australian adults obtained similar scores on all parts of TASIT. The older British adults though, obtained significantly lower scores than the Australian younger adults on all parts of TASIT and when education was controlled for they obtained significantly lower scores than the British younger adults. Conclusions & Implications: The findings are discussed in the light of previous research that has found that older adults are worse than younger adults at social inferences. The findings of the current study suggest that caution should be used when using TASIT with older British adults to assess social perception abilities.